Incentives vs. selection in promotion tournaments: Can a designer kill two birds with one stone? - Wolfgang Höchtl; Rudolf Kerschbamer; Rudi Stracke; Uwe Sunde (Institute for the Study of Labor (IZA), 2011)
This paper studies the performance of promotion tournaments with heterogeneous participants in two dimensions: incentive provision and selection. Our theoretical analysis reveals a trade-off for the tournament designer between the two goals: While total effort is maximized if less heterogeneous participants compete against each other early in the tournament, letting more heterogeneous participants compete early increases the accuracy in selection. Experimental evidence supports our theoretical findings, indicating that the optimal design of promotion tournaments crucially depends on the objectives of the tournament designer. These findings have important implications for the optimal design of promotion tournaments in organizations.
urn:nbn:de:101:1-201106202087
Keywords: M52; J33; 330; promotion tournaments; heterogeneity; incentive provision; selection